Spintronics: bacis principles and applications - Olarte, J. A.; Cifuentes, M. C. (Visión electrónica, 2014)
Spintronics often referred to the study of electron spins. This paper presents an overview of this theory and the basic physical principles that account for the behavior of the electron spins. The first part is focuses on the physical principles by which to generate spin-polarized currents, spin dynamics and transport in semiconductors. The second part presents some practical applications, such as: spin valves and magnetic tunnel junctions, which are currently being developed and focus the expectation of memory and information storage future devices.